Effects of employment protection on worker and job flows: evidence from the 1990 Italian reform - Adriana D. Kugler; Giovanni Pica (Institute for the Study of Labor (IZA), 2005)
This paper uses the Italian Social Security employer-employee panel to study the effects of the Italian reform of 1990 on worker and job flows. We exploit the fact that this reform increased unjust dismissal costs for firms below 15 employees, while leaving dismissal costs unchanged for bigger firms, to set up a natural experiment research design. We find that the increase in dismissal costs decreased accessions and separations for workers in small relative to big firms, especially in sectors with higher employment volatility. Moreover, we find that the reform reduced firms' employment adjustments on the internal margin as well as entry rates while increasing exit rates.
Keywords: E24; J63; J65; 330; unjust dismissal costs; European unemployment; firms' entry and exit; employment volatility; Kündigungsschutz; Arbeitsmarktflexibilisierung; Wirkungsanalyse; Arbeitsmobilität; Beschäftigungseffekt; Schätzung; Italien